2012
DOI: 10.1002/jclp.20864
|View full text |Cite
|
Sign up to set email alerts
|

Student Ratings of Selection Factors for PsyD Programs

Abstract: PsyD students rated a program's structure, tone, and reputation as particularly important factors to consider in selecting a program. Students' quality ratings were used to determine the top 5 programs for each of the factors assessed in the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The original distinction between the degrees-the extent to which clinical versus research training is emphasized (Korman, 1974;Norcross, Castle, Sayette, & Mayne, 2004;Peterson, 1976Peterson, , 1982)-may still be prominent and well recognized, but a growing body of research identifies a long list of additional, important distinctions. Specifically, researchers have found that in general, compared to PhD programs, PsyD programs tend to accept and enroll more applicants (with lower average grade point averages [GPAs] and Graduate Record Examination [GRE] scores); operate more often in free-standing institutions rather than university departments; provide less funding (e.g., assistantships, tuition remission), yielding greater costs to students; accept a higher percentage of students who already have a master's degree; have a lower success rate placing their students in American Psychological Association (APA)-accredited predoctoral internships; have a lower average length of time to degree completion; have alumni who are more likely to pursue careers in practice rather than research or academia; and have different percentages of faculty subscribing to certain theoretical orientations (e.g., higher psychodynamic, lower cognitive-behavioral; Dornfeld, Green-Hennessy, Lating, & Kirkhart, 2012;Gaddy, Charlot-Swilley, Nelson, & Reich, 1995;Graham & Kim, 2011;Klonoff, 2011;Mayne, Norcross, & Sayette, 1994;McFall, 2006;Norcross & Castle, 2002;Norcross & Sayette, 2014;Norcross, Sayette, Mayne, Karg, & Turkson, 1998). (It should be noted here, as it is in many of the studies cited above, that there is great heterogeneity within the PhD and PsyD categories.…”
mentioning
confidence: 99%
“…The original distinction between the degrees-the extent to which clinical versus research training is emphasized (Korman, 1974;Norcross, Castle, Sayette, & Mayne, 2004;Peterson, 1976Peterson, , 1982)-may still be prominent and well recognized, but a growing body of research identifies a long list of additional, important distinctions. Specifically, researchers have found that in general, compared to PhD programs, PsyD programs tend to accept and enroll more applicants (with lower average grade point averages [GPAs] and Graduate Record Examination [GRE] scores); operate more often in free-standing institutions rather than university departments; provide less funding (e.g., assistantships, tuition remission), yielding greater costs to students; accept a higher percentage of students who already have a master's degree; have a lower success rate placing their students in American Psychological Association (APA)-accredited predoctoral internships; have a lower average length of time to degree completion; have alumni who are more likely to pursue careers in practice rather than research or academia; and have different percentages of faculty subscribing to certain theoretical orientations (e.g., higher psychodynamic, lower cognitive-behavioral; Dornfeld, Green-Hennessy, Lating, & Kirkhart, 2012;Gaddy, Charlot-Swilley, Nelson, & Reich, 1995;Graham & Kim, 2011;Klonoff, 2011;Mayne, Norcross, & Sayette, 1994;McFall, 2006;Norcross & Castle, 2002;Norcross & Sayette, 2014;Norcross, Sayette, Mayne, Karg, & Turkson, 1998). (It should be noted here, as it is in many of the studies cited above, that there is great heterogeneity within the PhD and PsyD categories.…”
mentioning
confidence: 99%